2012
DOI: 10.1007/s11096-011-9605-z
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing practice in the community pharmacies in the Turkish Republic of Northern Cyprus

Abstract: The dispensing practice in the community pharmacies in the Turkish part of Cyprus seems inadequate in terms of GPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 18 publications
8
49
4
Order By: Relevance
“…We found that 39 was the mean number of individuals assisted by dispenser per day [min = 32; max = 44] and 7.6 min was the average dispensing time [min = 6.9; max = 9.5 min]. Authors studying the average dispensing time in several settings in Brazil and worldwide have found figures varying from less than one minute to almost 9 minutes 27,[45][46][47][48] . Nevertheless, WHO recommends at least 3 minutes for the orientation of each patient 49 , less than half the estimated time in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 39 was the mean number of individuals assisted by dispenser per day [min = 32; max = 44] and 7.6 min was the average dispensing time [min = 6.9; max = 9.5 min]. Authors studying the average dispensing time in several settings in Brazil and worldwide have found figures varying from less than one minute to almost 9 minutes 27,[45][46][47][48] . Nevertheless, WHO recommends at least 3 minutes for the orientation of each patient 49 , less than half the estimated time in our study.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 However, studies show that in addition to training issues, there are other aspects that influence the quality of services, such as working conditions (heavy commitment to the logistics process), the new culture of providing quick services, and preexisting patient expectations. 45,46 We acknowledge that some pharmacists in this study provided some good advice to the SPs; for example, most of the pharmacists referred the pregnant SP to a physician. This behavior was in keeping with the guidelines on expected outcomes provided by the expert panel in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients form positive or negative attitudes about health care professionals by drawing on their experience with the disease, treatment, and services provided. 46 Taking these experiences into consideration is critical to meeting patients' needs. 62,63 Thus, the role of the pharmacists should change from that of a paternalistic counselor to a counselor who supports the patient emotionally and helps them to combine actions, knowledge, and feelings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in many developing countries, in the Turkish Republic of Northern Cyprus (TRNC) pharmacists have a distinct role in pharmaceutical care and patient education since many patients attend pharmacies as a primary care in the health system (10). The need for qualified pharmacy services enforce for the improvement of teaching methods in pharmacy education.…”
Section: Introductionmentioning
confidence: 99%